The National MDS Natural History Study: design of an integrated data and sample biorepository to promote research studies in myelodysplastic syndromes. Issue 13 (10th November 2019) - Sekeres, Mikkael A.; Gore, Steven D.; Stablein, Donald M.; DiFronzo, Nancy; Abel, Gregory A.; DeZern, Amy E.; Troy, Jesse D.; Rollison, Dana E.; Thomas, John W.; Waclawiw, Myron A.; Liu, Jane Jijun; Al Baghdadi, Tareq; et al.
Abstract: Myelodysplastic syndromes (MDS), a spectrum of heterogeneous hematopoietic stem cell diseases, vary in clinical severity, response to therapy, and propensity toward progression to acute myeloid leukemia. These are acquired clonal disorders resulting from somatic mutations within the hematopoietic stem or progenitor cell population. Understanding the natural history and the risk of developing leukemia and other adverse outcomes is dependent on access to well-annotated biospecimens linked to robust clinical and molecular data. To facilitate the acquisition and distribution of MDS biospecimens to the wider scientific community and support scientific discovery in this disease, the National MDS Natural History study was initiated by the National Heart, Lung, and Blood Institute (NHLBI) and is being conducted in collaboration with community hospitals and academic medical centers supported by the National Cancer Institute (NCI). The study will recruit up to 2000 MDS patients or overlapping myeloproliferative neoplasms (MDS/MPN) and up to 500 cases of idiopathic cytopenia of undetermined significance (ICUS). The National MDS Natural History Study (NCT02775383) will offer the world's largest disease-focused tissue biobank linked to longitudinal clinical and molecular data in MDS. Here, we report on the study design features and describe the vanguard phase of 200 cases. The study assembles a comprehensive clinical database, quality of life results, laboratory data, histopathology slides and images, genetic information, hematopoietic and germline tissues representing high-quality biospecimens and data from diverse centers across the United States. These resources will be available to the scientific community for investigator-initiated research.